What is the relationship between ED patient anxiety level and patient sureness of medication history?. Issue 10 (October 2017) - Shapiro, Marcia; Speroni, Karen Gabel; Edsall, D. Renee; Daniel, Marlon G.
Abstract : How patients' anxiety levels affect the accuracy of medication reconciliation